Outbreak of High-Risk Clone ST323 Klebsiella pneumoniae Resistant to Ceftazidime–Avibactam Due to Acquisition of blaVEB-25 and to Cefiderocol Due to Mutated fiu Gene - Irene Galani; Ilias Karaiskos; Maria Souli; Vassiliki Papoutsaki; Aikaterini Gkoufa; Anastasia Antoniadou; Helen Giamarellou (Antibiotics)
Background/Objectives: The incidence of Ceftazidime/Avibactam (CZA)-resistant Klebsiella pneumoniae isolate co-producing Klebsiella pneumoniae carbapenemase 2 (KPC-2) and Vietnamese extended-spectrum β-lactamase 25 (VEB-25) has been on the rise in Greece over the past five years. This study investigates the isolation of ST323 K. pneumoniae isolates co-resistant to CZA and cefiderocol (FDC) from colonized and infected patients in a single hospital in Athens. Methods: CZA-resistant K. pneumoniae strains were isolated from 5 ICU patients from 27 December 2023 to 22 January 2024. Antimicrobial susceptibility was tested against a panel of agents. Whole-genome sequencing of the isolates was carried out to identify the acquired resistance genes and mutations that were associated with CZA and FDC resistance. Results: The K. pneumoniae isolates belonged to ST323 and harbored blaKPC-2 and blaVEB-25. The isolates had a minimum inhibitory concentration (MIC) of >256 mg/L for CZA and 32 mg/L for FDC, due to the disrupted catecholate siderophore receptor Fiu. blaVEB-25 was located on an IncC non-conjugative plasmid and on a ~14 kb multidrug resistance (MDR) region comprising 15 further acquired resistance genes. Transformation studies showed that the blaVEB-25-carrying plasmid provided resistance to most of the β-lactams tested, including CZA. The isolates remained susceptible to carbapenems, imipenem/relebactam, and meropenem/vaborbactam. The plasmid harbored the citrate-dependent iron (III) uptake system (fecIRABCDE), which increased the MIC of FDC from ≤0.08 mg/L to 2 mg/L. Conclusions: The blaVEB-25 gene was associated with IncC plasmids which are important contributors to the spread of key antibiotic resistance genes. Strict infection control measures must be elaborated upon to prevent the spread of extensively drug-resistant organisms such as those described here.